2019
DOI: 10.1111/gere.12294
|View full text |Cite
|
Sign up to set email alerts
|

New‐Build Development and the Gentrification of Oklahoma City's Deep Deuce Neighborhood

Abstract: New-build development has become associated with the phase of gentrification that has taken shape since the mid-1990s. This article examines the gentrification of Deep Deuce, a historically black neighborhood in Oklahoma City. An analysis of property sales identifies the major external agents involved and leads to a discussion of the area's racial turnover. Considering the relational aspects of place, specifically how the identity of Deep Deuce has been constructed in relation to the nearby area of Bricktown, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the literature of geographies of religion, there are debates on how secularization leads to church redevelopment, including the (de-)/(re-)making of sacred spaces, the marketisation of religion, the socio-spatial process resulted from diminishing role of the church in secularizing societies, the declining church membership, and the abandoned church buildings (Cimino, 2011, Hackworth and Gullikson, 2013, Lynch, 2016, Martin and Ballamingie, 2016, Mian, 2008, Payne and Greiner, 2019, Velthuis and Spennemann, 2007. These works offer numerous insights for us to explore further.…”
Section: Church Redevelopment and The Complexities Of Secularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature of geographies of religion, there are debates on how secularization leads to church redevelopment, including the (de-)/(re-)making of sacred spaces, the marketisation of religion, the socio-spatial process resulted from diminishing role of the church in secularizing societies, the declining church membership, and the abandoned church buildings (Cimino, 2011, Hackworth and Gullikson, 2013, Lynch, 2016, Martin and Ballamingie, 2016, Mian, 2008, Payne and Greiner, 2019, Velthuis and Spennemann, 2007. These works offer numerous insights for us to explore further.…”
Section: Church Redevelopment and The Complexities Of Secularizationmentioning
confidence: 99%
“…Researchers observed that religious organizations are actively involved in urban redevelopment in various ways, such as rebuilding their places of worship, selling their properties to finance charity services, and partnering with property developers for redevelopment. Albeit adaptive reuse of church buildings as an alternative to redevelopment is observed (Lynch, 2016, Martin and Ballamingie, 2016, Payne and Greiner, 2019, a large proportion of religious organizations tends to suggest demolishment of redundant churches as the best option because churches should not be reused in ways other than offering religious services (Velthuis and Spennemann, 2007). Mian (2008) shows both churches and developers in a partnership can gain benefits, thus resulting in a 'win-win' situation.…”
Section: Church Redevelopment and The Complexities Of Secularizationmentioning
confidence: 99%
“…The commonality of these urban regeneration projects, regardless of their formal objectives, is that they are generally initiated by the public sector, but often rely on the entrepreneurial governance model [28], meaning that property-led private initiatives most frequently act as their driving force [29,30]. As urban regeneration "is about land use, particularly ways of improving the [land] value" [31] (p. 110), the decision to demolish is thus "often influenced by land prices and market demand instead of the technical quality" of buildings [27] (p. 544).…”
Section: Introductionmentioning
confidence: 99%